A new closed-vessel conductively heated digestion system: fostering plant analysis by inductively coupled plasma optical emission spectroscopy - Miranda, Kelber [UNESP]; Pereira-Filho, Edenir Rodrigues; Gomes Neto, José Anchieta [UNESP] (Royal Soc Chemistry, 2014)
Open-vessel acid digestion is a low cost and easily automated sample decomposition method commonly used in laboratories involved in routine plant analysis. However, large amounts of reagents are required, the decomposition efficiency is limited by the boiling point of the digestion mixture and sample contamination and losses of volatile elements can frequently occur. In addition, the venting of large amounts of acid fume is undesirable due to its impact on the analyst and environment. For this reason, a simple, rugged and low cost closed-vessel conductively heated digestion system was developed and evaluated. The system accommodates 38 reaction vessels and enables the digestion of 200 mg of plant samples for subsequent elemental determination. The digestion procedure was optimized with the help of video images. The accuracy was confirmed by analyzing five certified reference materials digested by the proposed system. The digestion efficiency was evaluated by determining the residual carbon content and residual acidity. When plant samples were digested using the proposed system, results for Al, B, Ca, Cu, Fe, K, Mg, Mn, P, S and Zn by inductively coupled plasma optical emission spectroscopy were in agreement with those obtained after closed-vessel microwave-assisted digestion.